KORELASI RASIO LINGKAR PINGGANG PANGGUL (RLPP) TERHADAP PROFIL LIPID PADA PRA-GERIATRI DAN GERIATRI - Linawati Yunita; Dita Maria Virginia (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2014)
Abstract: Abnormality of lipid profile is one of cardiovascular risk factors which increases with aging.Anthropometric measurement is one of the predictors of abnormal lipid profile without invasive methodsand affordable cost. One of the anthropometric measurements that could be used as a predictor is waist tohip ratio (WHR). The aim of this study was to determine the correlation between WHR with abnormality oflipid profile which were related to total cholesterol, Low Density Lipoprotein (LDL), High DensityLipoprotein (HDL), and triglyceride (TG) in pre-geriatrics and geriatrics group. This study was analyticalobservational with cross sectional design. Statistical analysis used Kolmogorov-Smirnov followedbivariable analysis with confidence interval (CI) 95%. The correlation statistical test used Pearson andSpearman. The results showed no statistically significant correlation between WHR with total cholesterol(r=-0.054, p 0.05), LDL (r=-0.047, p 0.05), TG (r=0.018, p 0.05), and HDL (r=0.016, p 0.05).Keywords: lipid profile, waist-to-hip ratio (WHR), pre-geriatric, geriatri